O Código Técnico Como Fundamento De Uma Política Tecnológica Nacional: Uma Perspectiva Do Construtivismo Crítico De Andrew Feenberg - Oliveira, Fernando Honorato de (2024)
Thesis of the theoretical possibilities for the design of a technological policy applicable to the Brazilian reality. Considering the standards defined by hegemonically imposed social values, the thesis determines the theoretical possibility of using philosophical conceptual parameters through technical codes, as foreseen by Andrew Feenberg's Critical Theory of Technology/Critical Constructivism, to support the development of a national technology policy that defines elements applicable to the Brazilian socio-economic reality, through the planned expansion of technical knowledge and the democratization of access to technology. The thesis demonstrate that the various possible standards of technical codes reflect arrivisme and impose rules that are not always in the interest of the country, but that can be opened to the democratic inclusion of legitimate values and needs of society, to allow technology to be an aggregator of values that allows the cultural, economic, political and social development of the nation, through the use of resources available in its structure. The thesis connects the concepts of Andrew Feenberg and José Walter Bautista Vidal, highlighting the philosophical congruence of both in establishing viable parameters for an effective Brazilian technological policy.